Silicon-oxygen negative electrode slurry and preparation method thereof
By adding weak acid and specific binder to the slurry process of silicon oxygen negative electrode material, combined with the use of conductive agent and water, the gas generation problems caused by volume expansion and prelithiation of silicon oxygen negative electrode material during charging and discharging are solved, and the gas generation problems caused by volume expansion and prelithiation of silicon oxygen negative electrode material is improved. The stability and safety of the battery are met and the performance needs of high-energy-density batteries are met.
Patent Information
- Application Number
- CN202411283715.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2024-12-17
AI Technical Summary
The volume expansion of the silicon oxygen negative electrode material during charging and discharging leads to powdering, and prelithiation causes the residual lithium source on the surface of the material to react with the slurry to release gas, resulting in battery performance attenuation and safety hazards, which are difficult for traditional binders to solve these problems.
During the slurrying process, weak acid and suitable types of binders, such as a mixture of polyacrylic acid and styrene butadiene rubber, combined with conductive agent and water, and through specific mixing process and temperature control, good rheology performance and stability are prepared. The silicon oxygen negative electrode slurry can avoid gas generation and improve battery safety.
Effectively solve the problem of gas generation when prelithiated silicon oxygen active substances, improve the stability and rheological performance of the negative electrode slurry, simplify the coating process, reduce the safety hazards of the battery, and improve the high-energy density battery performance.
Smart Images

Figure BDA0005042467680000081
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of negative electrode materials, and in particular to a silicon-oxygen negative electrode slurry and a preparation method thereof. Background Art
[0002] With the booming market of portable electronic devices and electric vehicles, the demand for high energy density batteries is becoming increasingly urgent. Silicon oxide materials are regarded as highly promising negative electrode materials because of their high theoretical capacity. However, silicon oxide negative electrode materials face many challenges in practical applications. Especially during the charging and discharging process, their volume will expand significantly, causing the material to be easily pulverized, which in turn causes the battery performance to decay rapidly. More importantly, since pre-lithiation can greatly improve the first coulomb efficiency of silicon oxide negative electrode materials, silicon oxide negative electrode materials can generally be used to refer to or include pre-lithiated silicon oxide negative electrode materials. In the process of making negative electrode slurry, the residual lithium source on the surface of silicon oxide negative electrode materials will dissolve in the slurry, and react with the binder CMC, nano silicon, water and other substances in the slurry, continuously releasing gas, resulting in the inability to completely eliminate bubbles in the defoaming stage of the negative electrode slurry. After coating, the negative electrode sheet continues to produce gas during placement, causing cracks, pores and other defects in the coating. Even after being assembled into a battery, a small amount of gas is still produced, which will bring safety hazards and seriously restrict its application in high energy density batteries. Traditional binder CMC is unable to cope with these challenges of silicon-oxygen negative electrode materials and is unable to meet the market's growing demand for high-performance batteries. Summary of the invention
[0003] Based on the technical problems existing in the background technology, the present invention proposes a silicon-oxygen negative electrode slurry and a preparation method thereof. The present invention can solve the problem of easy gas generation in the pre-lithiation silicon-oxygen active material slurry in situ by adding a weak acid and a suitable type of binder during the slurrying process, and can make the negative electrode slurry have suitable rheological properties and stability, facilitate the subsequent coating process, and alleviate safety hazards.
[0004] The present invention provides a silicon-oxygen negative electrode slurry, wherein the raw materials thereof include, by weight: 91.5-92.5 parts of active material, 3.5-5.5 parts of binder, 1.0-2.5 parts of conductive agent, 0.5-1.0 parts of weak acid, and 100-105 parts of water;
[0005] The raw materials of the active material include, by weight: 72-74.5 parts of graphite and 18-20.5 parts of silicon-oxygen active material.
[0006] Preferably, the binder is a mixture of substance A and styrene-butadiene rubber, wherein substance A is one or more of polyacrylic acid and polyacrylate.
[0007] The polyacrylate salt may be sodium polyacrylate, lithium polyacrylate, potassium polyacrylate or the like.
[0008] The polyacrylic acid and polyacrylic acid salt are polyacrylic acid emulsion and polyacrylic acid salt emulsion respectively, and the solid content thereof is 7-10wt%.
[0009] The above-mentioned styrene-butadiene rubber is a styrene-butadiene rubber emulsion with a solid content of 35-45wt%.
[0010] Preferably, the weight ratio of substance A to styrene-butadiene rubber is 3-4:1.
[0011] Preferably, the weak acid is one or more of boric acid, phosphoric acid, aluminic acid, acetic acid, propionic acid, and acrylic acid.
[0012] The present invention selects polyacrylic acid or its salt and styrene-butadiene rubber to be matched with each other in an appropriate ratio, so that the negative electrode slurry has good rheology and viscosity, and is matched with a suitable type of weak acid to avoid the problem of gas generation during slurry mixing, so that the negative electrode slurry has good stability, facilitates the subsequent coating process, and improves the safety of the battery.
[0013] Preferably, the conductive agent is one or more of conductive carbon black SP, single-walled carbon nanotubes, multi-walled carbon nanotubes, and graphene.
[0014] The above-mentioned single-walled carbon nanotubes, multi-walled carbon nanotubes and graphene refer to their respective corresponding water-based slurries, and the solid content of the water-based slurries can be 0.4-4wt%.
[0015] Preferably, the silicon-oxygen active material is SiO x , where 0<x≤2.
[0016] Preferably, the silicon-oxygen active material is SiO2, SiO 1.3 、SiO 1.0 、SiO 0.85 、SiO 0.4 One or more of .
[0017] Preferably, the silicon-oxygen active material is a pre-lithiated silicon-oxygen active material.
[0018] Preferably, the viscosity of the silicon-oxygen negative electrode slurry is 2000-4000 mPa·s.
[0019] The solid content of the silicon-oxygen negative electrode slurry is 37-40wt%.
[0020] The present invention also proposes a method for preparing the above-mentioned silicon-oxygen negative electrode slurry, comprising the following steps: mixing graphite, silicon-oxygen active material, and part of the conductive agent once, adding part of the binder, weak acid, and part of the water and mixing them twice, then adding the remaining conductive agent and mixing them three times, adding part of the water and mixing them four times, homogenizing, then adding the remaining water and mixing them five times, and finally adding the remaining binder and mixing them six times to obtain the silicon-oxygen negative electrode slurry.
[0021] Preferably, after the second mixing, the solid content is 55-63 wt %.
[0022] The solid content after the three mixings can be 48-53 wt %.
[0023] Preferably, after four mixings, the solid content is 40-45 wt%.
[0024] Preferably, a double planetary stirring device is used for mixing.
[0025] Preferably, during the first mixing, the revolution speed is 40-50 rpm, the rotation speed is 0 rpm, and the mixing time is 80-100 min.
[0026] Preferably, during the secondary mixing, the revolution speed is 40-50 rpm, the rotation speed is 1500-2000 rpm, and the mixing time is 80-100 min.
[0027] Preferably, during the three mixing steps, the orbital speed is 80-90 rpm, the rotation speed is 4000-4500 rpm, and the mixing time is 80-100 min.
[0028] Preferably, during the four mixings, the orbital speed is 80-90 rpm, the rotation speed is 4000-4500 rpm, and the mixing time is 160-200 min.
[0029] Preferably, during homogenization, the orbital speed is 20-25 rpm, the rotational speed is 0 rpm, and the mixing time is 90-120 min.
[0030] Preferably, during the five mixings, the orbital speed is 80-90 rpm, the rotation speed is 4000-4500 rpm, and the mixing time is 20-100 min.
[0031] Preferably, during the six mixings, the orbital speed is 40-50 rpm, the rotation speed is 3000-3500 rpm, and the mixing time is 30-40 min.
[0032] Preferably, the three to six mixings are performed in a vacuum environment at a mixing temperature of 10-45°C.
[0033] The present invention selects a suitable slurry mixing process to further reduce the gas generation problem of the negative electrode slurry and improve the stability of the negative electrode slurry.
[0034] During the above three to six times of mixing, the mixing temperature can be adjusted by a circulating cooling water system.
[0035] The above water is all deionized water.
[0036] The present invention adds a weak acid and a suitable type of binder during the slurry mixing process, so that the slurry does not contain the traditional binder carboxymethyl cellulose CMC. The weak acid and the binder cooperate with each other to solve the problem of easy gas generation in the slurry mixing of pre-lithiation silicon oxygen active materials in situ, and can make the negative electrode slurry have suitable rheological properties and stability, facilitate the subsequent coating process, and alleviate safety hazards. DETAILED DESCRIPTION
[0037] The technical solution of the present invention is described in detail below through specific embodiments.
[0038] Example 1
[0039] A silicon-oxygen negative electrode slurry, the raw materials of which include, by weight: 73.5 parts of graphite, SiO 1.0 19 parts, 3.75 parts of sodium polyacrylate emulsion with a solid content of 10wt%, 1 part of styrene-butadiene rubber emulsion with a solid content of 40wt%, 1.9 parts of conductive carbon black SP, 0.1 part of single-walled carbon nanotube aqueous slurry with a solid content of 0.4wt%, 0.75 parts of boric acid, and 105 parts of water.
[0040] The method for preparing the silicon-oxygen negative electrode slurry comprises the following steps:
[0041] Graphite, SiO 1.0 1. Add conductive carbon black SP into a double planetary mixer, adjust the revolution speed to 45 rpm and the rotation speed to 0 rpm, and mix once for 90 minutes;
[0042] Then, sodium polyacrylate emulsion, boric acid and part of water were added, and the revolution speed was adjusted to 45 rpm and the rotation speed was adjusted to 1750 rpm, and secondary mixing was performed for 90 min to make the solid content 61 wt%;
[0043] Then, the single-walled carbon nanotube aqueous slurry was added, the revolution speed was adjusted to 85 rpm, the rotation speed was adjusted to 4250 rpm, and the mixing was performed three times for 90 min;
[0044] Add some water, adjust the revolution speed to 85 rpm, the rotation speed to 4250 rpm, and mix four times for 180 min to make the solid content 44 wt%;
[0045] The revolution speed was adjusted to 22 rpm and the rotation speed was adjusted to 0 rpm, and the slurry was homogenized for 105 min. At this time, the slurry viscosity was > 20000 mPa·s;
[0046] Add the remaining water, adjust the orbital speed to 85 rpm and the rotational speed to 4250 rpm, and mix five times for 60 min;
[0047] Finally, styrene-butadiene rubber latex was added, the revolution speed was adjusted to 45 rpm, the rotation speed was adjusted to 3250 rpm, and six mixings were performed for 35 min. After filtering, a silicon-oxygen negative electrode slurry with a viscosity of 3950 mPa·s and a solid content of 38.1 wt% was obtained. Among them, the third to sixth mixings were performed in a vacuum environment at a mixing temperature of 35°C.
[0048] Example 2
[0049] A silicon-oxygen negative electrode slurry, the raw materials of which include, by weight: 73.5 parts of graphite, silicon-oxygen active material (composed of SiO 0.85 and SiO 1.3 The invention discloses a method of preparing the present invention comprising the following steps: preparing the present invention comprises the following steps: (1) 19 parts of an aqueous solution of polyacrylic acid having a solid content of 10 wt %, (2) 4 parts of a lithium polyacrylate emulsion having a solid content of 10 wt %, (3) 1 part of a styrene-butadiene rubber emulsion having a solid content of 40 wt %, (4) 1.8 parts of conductive carbon black SP, (5) 0.2 parts of an aqueous slurry of multi-walled carbon nanotubes having a solid content of 0.4 wt %, (6) 0.5 parts of phosphoric acid, and (7) 100 parts of water.
[0050] The method for preparing the silicon-oxygen negative electrode slurry comprises the following steps:
[0051] Graphite, SiO 0.85 、SiO 1.3 1. Add conductive carbon black SP into a double planetary mixer, adjust the revolution speed to 40 rpm and the rotation speed to 0 rpm, and mix once for 100 minutes;
[0052] Then, lithium polyacrylate emulsion, phosphoric acid and part of water were added, and the revolution speed was adjusted to 50 rpm and the rotation speed was adjusted to 2000 rpm, and secondary mixing was performed for 80 minutes to make the solid content 60 wt%;
[0053] Then, add the multi-walled carbon nanotube aqueous slurry, adjust the revolution speed to 90 rpm and the rotation speed to 4500 rpm, and mix three times for 80 min;
[0054] Add some water, adjust the revolution speed to 90 rpm and the rotation speed to 4500 rpm, and mix four times for 200 min to make the solid content 45 wt%;
[0055] The revolution speed was adjusted to 20 rpm and the rotation speed was adjusted to 0 rpm, and the homogenization was performed for 120 min;
[0056] Add the remaining water, adjust the orbital speed to 80 rpm and the rotational speed to 4000 rpm, and mix five times for 100 min;
[0057] Finally, styrene-butadiene rubber latex was added, the revolution speed was adjusted to 40 rpm, the rotation speed was adjusted to 3500 rpm, and six mixings were performed for 40 min. After filtering, a silicon-oxygen negative electrode slurry with a viscosity of 3800 mPa·s and a solid content of 37.9 wt% was obtained. Among them, the third to sixth mixings were performed in a vacuum environment at a mixing temperature of 35°C.
[0058] Example 3
[0059] A silicon-oxygen negative electrode slurry, whose raw materials include, by weight: 72 parts of graphite, 19.5 parts of SiO2, 3.6 parts of polyacrylic acid emulsion with a solid content of 10wt%, 0.9 parts of styrene-butadiene rubber emulsion with a solid content of 40wt%, 2 parts of graphene aqueous slurry with a solid content of 0.4wt%, 1 part of acrylic acid, and 103 parts of water.
[0060] The method for preparing the silicon-oxygen negative electrode slurry comprises the following steps:
[0061] Add SiO2 and part of graphene into a double planetary mixer, adjust the revolution speed to 50 rpm and the rotation speed to 0 rpm, and mix once for 80 min;
[0062] Then add polyacrylic acid emulsion, acrylic acid, and part of water, adjust the revolution speed to 40 rpm, the rotation speed to 1500 rpm, and perform secondary mixing for 100 min to make the solid content 59 wt%;
[0063] Then, the remaining graphene aqueous slurry was added, the revolution speed was adjusted to 80 rpm, the rotation speed was adjusted to 4000 rpm, and the mixing was performed three times for 100 min;
[0064] Add some water, adjust the revolution speed to 80 rpm and the rotation speed to 4000 rpm, and mix four times for 160 min to make the solid content 40 wt%;
[0065] The orbital speed was adjusted to 25 rpm and the rotational speed to 0 rpm, and the homogenization was performed for 90 min;
[0066] Add the remaining water, adjust the orbital speed to 80 rpm and the rotational speed to 4000 rpm, and mix five times for 20 min;
[0067] Finally, add styrene-butadiene rubber latex, adjust the revolution speed to 50 rpm, the rotation speed to 3000 rpm, mix six times for 30 minutes, filter, and obtain a silicon-oxygen negative electrode slurry with a viscosity of 3850 mPa·s and a solid content of 38 wt%. The mixing for three to six times is carried out in a vacuum environment, and the mixing temperature is 35°C.
[0068] Comparative Example 1
[0069] A silicon-oxygen negative electrode slurry, which does not contain boric acid and is otherwise the same as in Example 1.
[0070] Comparative Example 2
[0071] A silicon-oxygen negative electrode slurry is prepared by replacing a sodium polyacrylate emulsion with a solid content of 10 wt % with a polyvinyl alcohol aqueous solution with a mass fraction of 10 wt %, and the rest is the same as in Example 1.
[0072] Comparative Example 3
[0073] A silicon-oxygen negative electrode slurry, wherein boric acid is replaced by oxalic acid, and the rest is the same as in Example 1.
[0074] Comparative Example 4
[0075] A silicon-oxygen negative electrode slurry does not contain boric acid, and replaces the sodium polyacrylate emulsion with a solid content of 10wt% with a pre-gelled carboxymethyl cellulose glue with a mass fraction of 1.5wt%. Others are the same as in Example 1.
[0076] The SiO in the above Examples 1-3 and Comparative Examples 1-4 1.0 、SiO 0.85 、SiO 1.3 , SiO2 have been pre-treated.
[0077] The fineness, stability and gas generation of the negative electrode slurries prepared in Examples 1-3 and Comparative Examples 1-4 were tested, and the results are shown in Table 1-2.
[0078] Fineness detection method: Use a scraper fineness meter to test the slurry fineness. If the fineness is too large, the screen will be blocked when filtering the slurry, affecting the subsequent coating effect and causing the risk of coating scratches.
[0079] Stability detection method: Let the newly prepared negative electrode slurry stand for 24 hours, detect the viscosity of the slurry, and compare its viscosity change with the viscosity of the newly prepared negative electrode slurry; the calculation formula is: viscosity change rate = (initial viscosity - viscosity at 24 hours) / initial viscosity * 100%.
[0080] Let the newly prepared negative electrode slurry stand for 24 hours, then take the slurry from the upper and bottom layers of the cup for solid content testing. The absolute value of the difference in solid content between the upper and lower layers can reflect the sedimentation performance of the slurry.
[0081] Table 1 Test results of fineness and stability of negative electrode slurry
[0082]
[0083] Gas production test method (indirect drainage method):
[0084] Accurately weigh 10g of the prepared negative electrode slurry and put it into an aluminum-plastic bag with a size of 10*15cm. Vacuum seal the aluminum-plastic bag to ensure a good seal to prevent gas leakage;
[0085] Prepare a 10ml measuring cylinder and turn it upside down. Connect the mouth of the measuring cylinder to the aluminum-plastic bag, making sure the connection is well sealed so that the gas can only be discharged from the measuring cylinder; fix the measuring cylinder in a vertical position and make sure it is stable;
[0086] Add enough water to the measuring cylinder to fill it up and reach the zero scale line, and record the initial water level scale; then place the sealed aluminum-plastic bag at room temperature, observe the water level changes in the measuring cylinder at 4, 8, 12, and 24 hours, and record the water level scale corresponding to each time point;
[0087] Then calculate the difference between the water level scale recorded at each time point and the initial water level scale. The difference is the gas production at that time point and the gas production rate is calculated. The gas production rate = gas production / negative electrode slurry volume*100%.
[0088] Table 2 Gas production detection results
[0089] Gas production rate % 4h 8h 12h 24h Example 1 2 3 4 4 Example 2 3 5 7 8 Example 3 7 11 13 14 Comparative Example 1 19 43 61 88 Comparative Example 2 8 12 19 22 Comparative Example 3 5 8 10 11 Comparative Example 4 26 50 78 96
[0090] It can be seen from Table 1-2 that the negative electrode slurry of the present invention has good stability and low gas production rate.
[0091] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A silicon-oxygen negative electrode slurry, It is characterized in that The raw materials include, by weight: 91.5-92.5 parts of active material, 3.5-5.5 parts of binder, 1.0-2.5 parts of conductive agent, 0.5-1.0 parts of weak acid, and 100-105 parts of water; The raw materials of the active material include, by weight: 72-74.5 parts of graphite and 18-20.5 parts of silicon-oxygen active material.
2. The silicon-oxygen negative electrode slurry according to claim 1, It is characterized in that The binder is a mixture of substance A and styrene-butadiene rubber, wherein substance A is one or more of polyacrylic acid and polyacrylate; preferably, the weight ratio of substance A to styrene-butadiene rubber is 3-4:1; preferably, the weak acid is one or more of boric acid, phosphoric acid, aluminic acid, acetic acid, propionic acid, and acrylic acid; preferably, the conductive agent is one or more of conductive carbon black SP, single-walled carbon nanotubes, multi-walled carbon nanotubes, and graphene.
3. The silicon-oxygen negative electrode slurry according to claim 1 or 2, It is characterized in that The silicon-oxygen active substance is SiO x , wherein 0<x≤2; preferably, the silicon-oxygen active material is SiO 2 、SiO 1.3 、SiO 1.0 、SiO 0.85 、SiO 0.4 One or more of .
4. The silicon-oxygen negative electrode slurry according to any one of claims 1 to 3, It is characterized in that The silicon-oxygen active material is a pre-lithiated silicon-oxygen active material.
5. The silicon-oxygen negative electrode slurry according to any one of claims 1 to 4, It is characterized in that The viscosity of the silicon-oxygen negative electrode slurry is 2000-4000 mPa·s.
6. A method for preparing the silicon-oxygen negative electrode slurry according to any one of claims 1 to 5, It is characterized in that The method comprises the following steps: mixing graphite, silicon-oxygen active material and part of conductive agent once, adding part of binder, weak acid and part of water and mixing twice, then adding the remaining conductive agent and mixing three times, adding part of water and mixing four times, homogenizing, adding the remaining water and mixing five times, and finally adding the remaining binder and mixing six times to obtain silicon-oxygen negative electrode slurry.
7. The method for preparing the silicon-oxygen negative electrode slurry according to claim 6, It is characterized in that After the second mixing, the solid content is 55-63wt%; preferably, after the fourth mixing, the solid content is 40-45wt%.
8. The method for preparing the silicon-oxygen negative electrode slurry according to claim 6 or 7, It is characterized in that Double planetary stirring equipment is used for mixing.
9. The method for preparing the silicon-oxygen negative electrode slurry according to claim 8, It is characterized in that During the first mixing, the revolution speed is 40-50rpm, the rotation speed is 0rpm, and the mixing time is 80-100min; preferably, during the second mixing, the revolution speed is 40-50rpm, the rotation speed is 1500-2000rpm, and the mixing time is 80-100min; preferably, during the third mixing, the revolution speed is 80-90rpm, the rotation speed is 4000-4500rpm, and the mixing time is 80-100min; preferably, during the fourth mixing, the revolution speed is 80-90rpm, the rotation speed is 4000-4500rpm, and the mixing time is 160-200min; preferably, when homogenizing, the orbital speed is 20-25rpm, the rotation speed is 0rpm, and the mixing time is 90-120min; preferably, when mixing five times, the orbital speed is 80-90rpm, the rotation speed is 4000-4500rpm, and the mixing time is 20-100min; preferably, when mixing six times, the orbital speed is 40-50rpm, the rotation speed is 3000-3500rpm, and the mixing time is 30-40min.
10. The method for preparing the silicon-oxygen negative electrode slurry according to any one of claims 6 to 9, It is characterized in that The three to six mixing steps are performed in a vacuum environment at a mixing temperature of 10-45°C.
Citation Information
Cited By
Silicon-based negative electrode slurry, preparation method thereof, negative electrode plate and application
CN121546065A
